PENGARUH KESEIMBANGAN DAN TINGKAT USIA ANAK TUNAGRAHITA MAMPU DIDIK TERHADAP KEMAMPUAN MOTORIK KASAR - ARIF ROHMAN HAKIM (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2015)
Mental retardation children able students are children who have developmental delays but can learn in academic skills. The developmental delays also give impact in the development of motor skills. The motor skills of mental retardation children can be trained through exercise through use the proper training methods. AlphaThis study focused on the influence of age and balance training on hard motor skills in mental retardation children able learners. AlphaThe results: 1) there was no significant effect of age on hard motor skills in mental retardation children; 2) there was no significant effect of balance training on hard motor skills in mental retardation children, 3) no significant interaction effect of age and balance exercises on hard motor skills in mental retardation children. In this study concluded that age does not ensure that more children in motor skills would be better. The suggestion for teachers to implement continuous training in order to improve hard motor skills of children.